Social media platforms' responses to COVID-19-related mis- and disinformation: the insufficiency of self-governance - Lina Warnke; Anna-Lena Maier; Dirk Ulrich Gilbert (Journal of Management and Governance, 2024)
Abstract The spread of mis- and disinformation on social media platforms is a significant societal threat. During the COVID-19 pandemic, mis- and disinformation played an important role in counteracting public health efforts. In this article, we explore how the three most relevant social media platforms, Facebook, YouTube, and Twitter, design their (IT) self-governance as a response to COVID-19-related mis- and disinformation, and provide explanations for the limited scope of their responses. Exploring the under-researched connection between the operating principles of social media platforms and their limited measures against mis- and disinformation, we address a relevant research gap in the extant literature on digital platforms and self-governance, particularly the role of IT governance (ITG), providing the ground for our argument against an overreliance on self-governance. In our qualitative study that draws on publicly available documents, we find that the shortcomings of current responses to mis- and disinformation are partly due to the complex nature of mis- and disinformation, as well as the wider political and societal implications of determining online content's factuality. The core problem, however, is grounded in the current overreliance on self-governance. We argue for an enhanced dialogue and collaboration between social media platforms and their relevant stakeholders, especially governments. We contribute to the growing ITG literature and debate about platforms' roles and responsibilities, supporting the intensifying calls for governmental regulation.
Keywords: 330; COVID-19; Disinformation; IT governance; Misinformation; Self-governance; Social media platforms